TAXPAYER READINESS FOR FULLY DIGITAL TAX ADMINISTRATION MODELS - Loso Judijanto; Amirah Andika Rifdayanti (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2026)
Digital transformation in tax administration is one of the government's primary strategies to improve efficiency, transparency, and tax compliance. The implementation of a fully digital tax administration model requires taxpayers to be prepared to adopt various technology-based systems and services. This study aims to analyze the level of taxpayer readiness for the implementation of fully digital tax administration models and identify factors influencing this readiness. The study employed a literature review method, examining various scientific articles, institutional reports, and relevant policy documents regarding the digitalization of tax administration. The results indicate that taxpayer readiness is influenced by the level of digital literacy, perceived ease of use of the system, data security and protection, trust in tax authorities, the quality of technological infrastructure, and the effectiveness of government outreach and assistance. Furthermore, digitalization of tax administration has the potential to increase voluntary compliance, accelerate tax reporting and payment processes, and reduce administrative costs. However, the gap in technology access and digital capabilities among taxpayer groups remains a challenge that needs to be addressed. Therefore, a comprehensive strategy is needed through strengthening digital literacy, improving the quality of electronic services, and developing inclusive policies to support the successful implementation of digital tax administration across the board. This research provides a conceptual contribution to understanding the determinants of taxpayer readiness and its implications for the success of digital transformation in the tax sector.